The Role of Platelets in Cancer-Related Bleeding Risk: A Systematic Review - Larsen, Julie Brogaard; Hojbjerg, Johanne Andersen; Hvas, Anne-Mette (Seminars in Thrombosis and Hemostasis, 2020)
Cancer patients face an elevated risk of bleeding, and here platelets play a pivotal role. The association between platelet count and bleeding, as well as safe thresholds for prophylactic platelet transfusion, is described mainly in hematological malignancies, and knowledge is sparse for patients with solid tumors. Platelet function tests may further improve bleeding risk assessment in cancer patients. This study provides a systematic review of the available literature on associations between platelet count and/or function and bleeding in adult cancer patients. The review was performed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. PubMed, Embase, and Web of Science were searched up to August 2019. The National Heart, Lung, and Blood Institute's tools were used for quality assessment. In total, 52 studies investigated associations between bleeding and platelet count (n = 40) or function (n = 12) in patients with hematological malignancy (n = 31), solid tumors (n = 11), or both (n = 10). The majority of included studies rated good (n = 23) or fair (n = 25). The association between platelet count and bleeding was most pronounced at platelet counts ≤ 10 × 109/L but was less evident for solid tumors. Overall, reduced platelet function was significantly associated with bleeding risk. Thus, the available evidence supports current guidelines for prophylactic platelet transfusions at platelet count ≤ 10 × 109/L in hematological cancer patients, whereas more evidence is needed in patients with solid tumors. Platelet function analysis may be valuable in assisting bleeding risk assessment in cancer patients but is sparsely investigated so far.
Keywords: thrombocytopenia; platelet count; platelet function; neoplasms; hemorrhage